Exploring interpersonal meanings on the discourse of the Indonesian national anthem from the CDA perspectives - Ribut Surjowati (Universitas Syiah Kuala, 2021)
This research is aimed at describing how the composer of Indonesia Raya (IR) construed and negotiated interpersonal meanings which represent his ideology to the Indonesians. The data in this qualitative study was the text of IR which is ideologically contested. The study analyzed the lexicogrammar properties dealing with words and structures and production processes. The data were collected by the researcher as the research instrument by using a documentation technique. The procedures of data analysis were conducted following the stages of Fairclough’s Critical Discourse Analysis framework (1989), including micro analysis concerning lexical features in the text, meso analysis concerning the process production and interpretation of the text, and macro analysis concerning ideological effects and hegemonic processes in which discourse participates. The attitude system of appraisal was analyzed based on that proposed by Martin and White (2005), and Martin and Rose (2003). The results showed that from the affect viewpoint, the IR composer is seen as an educated young man who witnessed people suffer and did not only express his feeling of joy with the coming independence of Indonesia and the gratefulness, but also the insecurity and anxiety with the possibility of other forms of colonialism. Meanwhile, from the appreciation viewpoint, Indonesia is described as a noble, heredity, sacred, and magical land. Not only is it an expression of his admiration and love, but also it is a warning to maintain his emotional intimacy with the nation. The judgment subcategory illustrated that the Indonesians were mostly emotionally weak. The composer encouraged the Indonesian people to unite for a greater Indonesia.